2021
DOI: 10.2147/jir.s322430
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Plasma Proteome Induced by SARS-CoV-2 and MERS-CoV Reveal Biomarkers for Disease Outcomes for COVID-19 Patients

Abstract: This study aimed to understand the pathophysiology of host responses to infections caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/(COVID-19) and Middle East respiratory syndrome coronavirus (MERS-CoV) and to identify proteins for patient stratification with different grades of illness severity. Patients and Methods: Peripheral blood samples from 43 patients with different grades of COVID-19, 7 MERS-CoV patients admitted to the ICU, and 10 healthy subjects were analyzed using label-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…More recent studies of Alaiya et al (2021), Mardani et al (2022), and Tahery et al (2021) showed an elevated levels of CRP alongside other biomarkers in severe vs asymptomatic COVID-19 comparison groups, suggesting the plausibility of CRP as a severity and mortality marker for SARS-CoV-2 infection [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies of Alaiya et al (2021), Mardani et al (2022), and Tahery et al (2021) showed an elevated levels of CRP alongside other biomarkers in severe vs asymptomatic COVID-19 comparison groups, suggesting the plausibility of CRP as a severity and mortality marker for SARS-CoV-2 infection [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 99%
“…In this preliminary study, we describe, for the first time, the salivary proteome variations that can be observed in patients with COVID-19. The study of alterations in the plasma proteome of COVID-19 patients has been recently explored with the identification of some proteins that may act as promising biomarkers for the disease physiopathology 15 . Saliva is easier to collect than serum and can be a source of biomarkers for clinical use in COVID-19 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Alaiya et al. ( 66 ) provided a method to objectively predict disease outcome in severe COVID-19 patients using LC−MS/MS for identifying and quantifying proteomic expression in different degrees of COVID-19 peripheral blood samples from patients. They identified 49 differentially expressed proteins that were upregulated in the peripheral blood of critically ill patients; 9 of them were upregulated in asymptomatic patients, and 12 of them had predictive value for recovery from severe disease.…”
Section: Host Cell Proteomicsmentioning
confidence: 99%